Hydrodynamic and Thermal Study of Water in Narrow Copper Tube - Gupta, S.; Sharma, Abhishek; Singh, K.; Srivastava, K. (Anamaya Publishers, 2013)
Fluid flow and heat transfer phenomena in a copper narrow tube were experimentally investigated in this study. The aim of this study was thus to validate heat transfer and friction factor in the fully developed region for flow inside narrow smooth copper tube using water as the working fluid. An experimental investigation on heat transfer and friction factors was compared with data available in the open literature and the results were in good agreement. The hydrodynamic and thermal study successfully represented the nature of the systems. © 2013 Indian Institute of Chemical Engineers.